The Influence of Sand Pore Structure on Air Migration During Air-Injected Desaturation Process - Yumin Chen; Chengzhao Qin; Saeed Sarajpoor; Runze Chen; Yi Han; Zijun Wang (Buildings)
The air injection method serves as a liquefaction mitigation technique to improve the liquefaction resistance of the foundations by decreasing the degree of saturation. To investigate the desaturation effect of this technique in various soil strata of the foundation, thin plate model tests were conducted, considering the impacts of gradation and relative density, to visualize the air migration process and distribution. The findings reveal the following: (1) The air migration process, delineated by air injection parameters, comprises four distinct phases, with stages II and III notably influenced by the pore structure; (2) air migration is governed by the pore throat dimensions, particle arrangement, and connectivity within the pore structure, exhibiting two predominant patterns: channel flow, primarily driven by inertial forces, and chamber flow, predominantly influenced by viscous and capillary forces; (3) referring to the air injection port, the gas phase distribution within the sand samples is consistent in the horizontal direction but not in the vertical direction. The concentration area and uniformity of the gas phase distribution are controlled by the pore structure. These results suggest potential enhancements in the positioning of air injection ports within complex soil layers, as well as improvements in the construction process, both aimed at optimizing the desaturation effect.